Strategies for developing self-assembled nanoparticle vaccines against SARS-CoV-2 infection - Yang, Kaiwen; Zeng, Youqin; Wu, Xinyu; Li, Jia; Guo, Jinlin (Frontiers in Immunology, 2024)
In the recent history of the SARS-CoV-2 outbreak, vaccines have been a crucial public health tool, playing a significant role in effectively preventing infections. However, improving the efficacy while minimizing side effects remains a major challenge. In recent years, there has been growing interest in nanoparticle-based delivery systems aimed at improving antigen delivery efficiency and immunogenicity. Among these, self-assembled nanoparticles with varying sizes, shapes, and surface properties have garnered considerable attention. This paper reviews the latest advancements in the design and development of SARS-CoV-2 vaccines utilizing self-assembled materials, highlighting their advantages in delivering viral immunogens. In addition, we briefly discuss strategies for designing a broad-spectrum universal vaccine, which provides insights and ideas for dealing with possible future infectious sarbecoviruses.